THE EFFECT OF CURRENT VELOCITY ON SUBMARINE CABLE STABILITY IN LHOKSEUMAWE - MEDAN WATERS - Jauhari Pratama, Raihan
Indonesia is one of the countries that can utilize its waters as a place for laying submarine cable. In submarine cable installation, one of the factors that influence is the current velocity. This research focuses on analyzing the stability of the submarine cable in Lhokseumawe – Medan waters with environment factor considered is only current velocity. The stability analysis of the submarine cables in Lhokseumawe – Medan waters was carried out by calculating the lateral and vertical direction. The stability calculation of the vertical direction is obtained by comparing the specific gravity (SG) of the cable and sea water. Meanwhile, the calculation of lateral stability is obtained by calculating the difference in the weight forces of the cable and the environment forces. This study uses a 2-dimensional Delft3D-Flow model with simulations carried out for 12 months, from September 2010 to August 2011 and a time step of 10 minutes. The inputs used are tides and winds. The elevation verification model results have an RMSE value of 0.164 meters and an R2 value of 0.90. Meanwhile, the velocity verification of the u-direction and v-direction currents, the model results have an RMSE value of 0.085 m/s for the u direction and 0.113 m/s for the v direction and an R2 value of 0.89 for the u-direction and 0.90 for the v-direction. The three verification results indicate that the model results are quite good and can be used for calculating the stability of the cable. The highest current velocity is in the west monsoon (DJF) with a speed of 0.48 m/s so that the west monsoon is a season that needs more to worry about. The lift force is a force that is more dominant than inertia and drag. Based on this research, the stability of the vertical direction of the cable is in a stable condition, it is shown that the value of the cable SG is 2.90 which is greater than the SG for sea water of 1.02. Then the lateral direction stability is in a stable condition as indicated by the difference in cable weight forces and environmental force of more than 10% with a difference value ranging from 28 - 90%. The percentage difference between the stability of the submarine cable in the lateral direction increases with increasing depth, so that the deeper a water is, the more stable it is.